On course : a week-by-week guide to your first semester of college teaching - Lang, James M. (Harvard University Press, 2008)
Practical and lively, On Course is full of experience-tested, research-based advice for graduate students and new teaching faculty. It provides a range of innovative and traditional strategies that work well without requiring extensive preparation or long grading sessions when you're trying to meet your own demanding research and service requirements.